Vpliv finančnih sistemov na učinke finančne krize - Hafner, Marjan (IB revija (Ljubljana), 2013)
Before the outbreak of the international financial crisis, Slovenia and some other new EU members recorded high rates of economic growth, and were thus gradually narrowing their development gaps with the EU. However, during the financial crisis this process slowed significantly. In fact it almost came to a halt, an indication that the new EU members were more affected by the crisis than the older members. Using cluster analysis, the authors find that Slovenia is one of the EU countries that has been most heavily affected by the crisis. These countries typically have an underdeveloped financial system, where a greater role is played by banks that mainly provide debt financing at shorter maturities. Over the course of the financial crisis, this financing recorded the largest decline, which translated into an above-average slowdown in economic activity. Statistically significant differences between the countries where the impact was greater and those where it was smaller have thus been found, particularly in the developmental and structural indicators for the financial system, which indicates the significance of long-term financing to the economy. The authors conclude that the stability and development of financial systems could be an important factor in explaining the impact of the financial crisis in individual EU countries.
Keywords: finance; finančni sistemi; krize; finančna kriza; banke; gospodarska gibanja; EU; European Union; Evropska unija